Accelerating Digitalization : Critical Actions to Strengthen the Resilience of the Maritime Supply Chain - World Bank (World Bank, Washington, DC, 2021)
The Coronavirus disease 2019 (COVID-19) pandemic has upended lives and brought major disruption to economic activity across the world, precipitating an unprecedented global health and economic crisis. One of the key lessons learned early in the pandemic was the need to ensure business continuity of the critical supply lines, notably the maritime gateways, and the associated logistical chains. However, the maritime ports are also just one node in a complex logistical chain involving a number of interactions; digitization is vital to improving the competitiveness of that chain. A number of global organizations, such as United Nations Conference on Trade and Development (UNCTAD), United Nations Economic Commission for Europe (UNECE), World Customs Organization (WCO), World Trade Organization (WTO), and International Maritime Organization (IMO) have been advocating the accelerated digitalization of cross-border processes and documentation. This report highlights the immediate, short-, and medium-term measures considered necessary to strengthen the resilience of the maritime and logistics sector, to build back better, and more importantly ensure countries realize the significant potential efficiency gains of digitization. This report underlines digitalization as not solely a technological issue, but also as human capital and institutional issues. Any move towards increased digitization will require a high level of political commitment, while the establishment must have an appropriate legal, regulatory, and policy framework at the national level, across the different disciplines of the maritime, port, clearance agencies, and the transport and logistics sector.